ARAM H. SIMONYAN (Words of remembrance and appreciation) - Minasyan, Edik; Gharibyan, Alik (History and Culture, 2022)
The words of remembrance are dedicated to the famous Armenian scientist, historian, Aram Simonyan. The educational and scientific activities of the famous specialist of Armenian Studies have been presented, as well as his long-term merit has been appreciated. The work also refers to his published articles and monographs.
Keywords: Aram Simonyan; specialist in Armenian Studies; historian; YSU Rector; History of Zangezur; Correspondent Member of NAS RA